2021
DOI: 10.1002/cphc.202100348
|View full text |Cite
|
Sign up to set email alerts
|

Group 12 Carbonates and their Binary Complexes with Nitrogen Bases and FH2Z Molecules (Z=P, As, Sb): Synergism in Forming Ternary Complexes

Abstract: MCO 3 (M=Zn, Cd, Hg) forms a spodium bond with nitrogencontaining bases (HCN, NHCH 2 , NH 3 ) and a pnicogen bond with FH 2 Z (Z=P, As, Sb). The spodium bond is very strong with the interaction energy ranging from À 31 kcal/mol to À 56 kcal/mol. Both NHCH 2 and NH 3 have an equal electrostatic potential on the N atom, but the corresponding interaction energy is differentiated by 1.5-4 kcal/mol due to the existence of spodium and hydrogen bonds in the complex with NHCH 2 as the electron donor. The spodium bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…[4][5][6] Consequently, some interests have been focused on the structures, properties, nature, and applications of spodium bonds. [7][8][9][10][11][12][13][14][15][16][17][18][19] Joy and Jemmis [20] have pointed out that metals in Group 12 of the periodic table, acting as Lewis acids, may be involved in noncovalent interactions (NCIs) before the concept of spodium bond was raised. The first evidence for this type of bond was reported for the structure of dichloro-bis(thiosemicarbazide)-mercury(II) in 1977.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6] Consequently, some interests have been focused on the structures, properties, nature, and applications of spodium bonds. [7][8][9][10][11][12][13][14][15][16][17][18][19] Joy and Jemmis [20] have pointed out that metals in Group 12 of the periodic table, acting as Lewis acids, may be involved in noncovalent interactions (NCIs) before the concept of spodium bond was raised. The first evidence for this type of bond was reported for the structure of dichloro-bis(thiosemicarbazide)-mercury(II) in 1977.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The relatively big polarization energy stands for that the spodium bond has some amount of covalency; therefore, it is of interest to distinguish between the noncovalent spodium bond and the corresponding covalent bond. [10,11] In constructing supramolecular aggregates with spodium bonding, it is often found that this type of bonding coexists with other varieties of NCIs [12] ; for instance, Liu and coauthors [13][14][15][16] investigated the interplay between the spodium bond and other NCIs including hydrogen, halogen, pnicogen, chalcogen, and tetrel bonds. Similar to other NCIs, the electron donors in the spodium bond can also be quite diverse, ranging from molecules containing lone pairs and anions to π-electron molecules [17,18] and carbenes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter are characterized by the replacement of the bridging proton by any of a wide assortment of other atoms, most more electronegative than H. These interactions are commonly categorized in reference to the family of elements from which this replacement bridging atom is drawn. The chalcogen bond, for example, makes use of S, Se, and Te, while the involvement of P, As, or Sb leads to the designation as a pnicogen bond. …”
Section: Introductionmentioning
confidence: 99%